EFEKTIFITAS PENGGUNAAN MEDIA VIDEO BERBASIS LINGKUNGAN (MVBL) DALAMMENINGKATKAN PERILAKU POSITIF ANAK TERHADAP LINGKUNGAN - Widowati Anantasari; A. Wahab Jufri; Aos Santosa Hadiwijaya (Jurnal Penelitian Pendidikan IPA, 2015)
The positive attitude of students toward environment is the manifestation of a positive  attitude of students toward  the environment. The development of student  positive  attitude  toward  environment  can be gotten  through  the aplication of daily attitude  and the model  that student s catch and feel from the environment  where  student s live.  The students need to get the experiences and learn  by themselves with a possitive  attitude in order that they are accepted  by the environment and they  do not  do harm  their environment. The experiences  given to the student  should be prepared  to help them  to share, cooperate, respect, love renponsible,  and having  self confidance. This research aim at knowing  the difference of children’s  possitive attitude  toward environment at students who lern by using video media based environment  (VMBE). Will those who do not learn  by using video media  based  environment  (VMBE). Research  was aquasi  experimental  research with pretest and posttest control design. The data of students positive attitude  toward environment  were gotten  by using  observation  technique ( the observation of students  positive attitude improvement  ) The data of this research  were analyzed  by using the analysis of independent  sample t-test tecnique.The result of  analysis  can be  concluded as follows : with df : 16 at significant  level 0.05 showed that  there was  difference of students possitive attitude who learn by using  MVBL  than those  who did not  learn by using MVBL  (t=3.120)Keywords : VMBE, Possitive attitude toward environment.